Popliteal cyst - a case report - V K Sathidevi; U R Rahul; Arun K Aipe (Wolters Kluwer Medknow Publications, 2012)
The authors report a case of popliteal cyst which was detected during the routine dissection of a cadaver in Anatomy Department, Government Medical College, Thrissur, Kerala. The cyst was identified in the right popliteal fossa in a female cadaver arising from the interior of knee joint. It measured 6 cm in length and 3 cm in width. Thick synovial membrane was forming the cyst wall. On deep dissection it was found communicating directly with the synovial lining of knee joint.